2020
DOI: 10.3390/ma13092135
|View full text |Cite
|
Sign up to set email alerts
|

Dry Electrodes for Surface Electromyography Based on Architectured Titanium Thin Films

Abstract: Electrodes of silver/silver chloride (Ag/AgCl) are dominant in clinical settings for surface electromyography (sEMG) recordings. These electrodes need a conductive electrolyte gel to ensure proper performance, which dries during long-term measurements inhibiting the immediate electrode’s reuse and is often linked to skin irritation episodes. To overcome these drawbacks, a new type of dry electrodes based on architectured titanium (Ti) thin films were proposed in this work. The architectured microstructures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 42 publications
0
32
0
2
Order By: Relevance
“…Both types of electrodes can achieve equivalent signal quality [ 13 ], which makes dry electrodes more suitable for industrial applications. Novel types of dry electrodes based on architecture titanium thin films [ 14 ] or flexible hydrographic printed dry electrodes [ 15 ], that may be attached to the body similar to a tattoo, offer an alternative to conventional wet Ag/AgCl electrodes with improved biocompatibility, usability, and long-term wearability. Recently, conductive hydrogels electrodes have been developed to capture biosignals, such as EMG or ECG (ElectroCardoGram), accurately [ 16 ].…”
Section: Electromyographymentioning
confidence: 99%
“…Both types of electrodes can achieve equivalent signal quality [ 13 ], which makes dry electrodes more suitable for industrial applications. Novel types of dry electrodes based on architecture titanium thin films [ 14 ] or flexible hydrographic printed dry electrodes [ 15 ], that may be attached to the body similar to a tattoo, offer an alternative to conventional wet Ag/AgCl electrodes with improved biocompatibility, usability, and long-term wearability. Recently, conductive hydrogels electrodes have been developed to capture biosignals, such as EMG or ECG (ElectroCardoGram), accurately [ 16 ].…”
Section: Electromyographymentioning
confidence: 99%
“…Moreover, the use of soft, flexible substrate materials fosters the adaptivity of the electrode to the body shape, increasing the long-term wearing comfort and improving the electrode-skin contact, especially during body motion [3,[12][13][14]. Dry electrodes are thus user-friendly solutions offering improved applicability without the need for hydrogels or other types of wet electrolytes [3,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Production cost, complexity, and reproducibility as well as constraints in electrode shape, mechanical characteristics, and durability have limited these materials to prototypes thus far. Coated elastomers have been suggested primarily with Ag [24], Ag/AgCl [11,13,16,25], gold (Au) [26], and titanium (Ti) [17,27,28]. While silverbased coatings are known to provide excellent electrochemical and thus bioelectric signal characteristics, their biocompatibility in long-term repetitive applications remains an often discussed and questioned limitation [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the rapid development of textile electrodes is producing sensor-embedded clothing that is like conventional clothing without deteriorating the wearer’s comfort [ 14 , 15 ]. In the current study, electrodes made of both carbon and silver layers were assessed in considering that they satisfy several requirements that Rodrigues et al indicated in their study on titanium thin film-based electrodes: high corrosion, wear resistance, good mechanical ductility, chemical and thermal stability, and with high bio-compatibility [ 16 ]. In addition, a conductive sheet can be deposited over fabric with a heat press in a single step and electrodes and interconnector (electrical wire) can be produced at once.…”
Section: Introductionmentioning
confidence: 99%